2018
DOI: 10.3390/su10114302
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Vulnerability of Marine Fisheries in China: Towards an Inter-Provincial Perspective

Abstract: China’s marine fisheries are undergoing large-scale environmental changes associated with climate change, marine pollution, and overfishing. The assessment of marine fisheries vulnerability has become extremely necessary for fisheries management and sustainable development. However, studies on China’s marine fisheries vulnerability remains sparse. This study aimed to provide an analysis of the inter-provincial level vulnerability of China’s marine fisheries under multiple disturbances. The vulnerability measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The entropy weight method is popularly used in the multicriteria decision-making process (Chen et al 2018). For the present study, the weights are assigned separately to each variable of vulnerability function where the sum of weights for each function becomes 1.…”
Section: Entropy Weight Methods For LVImentioning
confidence: 99%
“…The entropy weight method is popularly used in the multicriteria decision-making process (Chen et al 2018). For the present study, the weights are assigned separately to each variable of vulnerability function where the sum of weights for each function becomes 1.…”
Section: Entropy Weight Methods For LVImentioning
confidence: 99%
“…The Asia-Pacific coastal regions face a range of anthropogenic threats, especially around heavily populated areas such coastal China [ 15 ]. It is well-recognized that healthy oceans and thriving coastal and freshwater ecosystems are essential for economic growth and food production [ 84 ].…”
Section: Future Trendsmentioning
confidence: 99%
“…Potential changes in marine resource distribution and abundance are significant in these densely populated tropical regions of high biodiversity, where small-scale fishing operations constitute more than 90% of the world’s fish traders. For example, the expanding Chinese marine fisheries are now suffering from the depletion of resources due to multiple anthropogenic threats, including overfishing, pollution and land reclamation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the perspective of food security, Ding et al (2017) analyzed the impact of climate change on the vulnerability of marine fisheries in 109 countries from three aspects: national exposure, sensitivity and adaptive capacity. Qi et al (2018) used a vulnerability model to assess the vulnerability of marine fisheries in 11 coastal provinces in China from three aspects: exposure, sensitivity and adaptive capacity. Kim et al (2018) compared the climatic vulnerability of coastal and inshore fisheries and found that the climatic vulnerability of coastal fisheries was higher than that of inshore fisheries.…”
Section: Literature Reviewmentioning
confidence: 99%